2014
DOI: 10.1111/1346-8138.12490
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal trophic syndrome: Report of a case and review of the published work

Abstract: Trigeminal trophic syndrome is a rare complication of trigeminal nerve injury that causes facial ulceration, anesthesia and paresthesia in the same trigeminal dermatomes. We present a case of a 65-year-old woman with a history of meningioma resection 18 years prior who presented 16 years later with an intractable ulceration around her left nasolabial sulcus. Pain and light-touch sensations around the ulcer were decreased. She admitted to frequent manipulation due to a crawling sensation. A skin biopsy showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 16 publications
1
59
0
4
Order By: Relevance
“…3 In addition, it has been reported that semaphorin 3A is strongly expressed in the lesion, suggesting that peripheral nerve fibres are negatively regulated by semaphorin 3A. 4 However, in our patient the numbers of neurofilament + or PGP9.5 + (Thermo Fisher, Rockford, IL, USA) peripheral nerve fibres in the periphery of the ulcer were significantly increased compared with those in normal individuals (neurofilament: Fig. 1c-e, PGP9.5: Fig.…”
mentioning
confidence: 46%
See 1 more Smart Citation
“…3 In addition, it has been reported that semaphorin 3A is strongly expressed in the lesion, suggesting that peripheral nerve fibres are negatively regulated by semaphorin 3A. 4 However, in our patient the numbers of neurofilament + or PGP9.5 + (Thermo Fisher, Rockford, IL, USA) peripheral nerve fibres in the periphery of the ulcer were significantly increased compared with those in normal individuals (neurofilament: Fig. 1c-e, PGP9.5: Fig.…”
mentioning
confidence: 46%
“…The physical examination requires the patient undergo a general skin examination 4 by a non-skin specialist. No currently available laboratory tests adequately detect leprosy.…”
mentioning
confidence: 99%
“…Decreased sensation often accompanies these paresthesias, which leads to severe disfigurement with repetitive manipulation of the area; however, one case series reported 50% of their patients had significant associated pain . The ulcers may be single or multiple, focal or extensive, and are reported more often on the right side of the face . The syndrome most commonly affects the second (maxillary) division of the trigeminal nerve and most commonly arises at the junction of the first and second divisions of the trigeminal nerve at the ala nasi .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Soft tissue scarring can draw the upper lip into a characteristic sneer . Eye lesions are more common than expected; TTS can often result in eyelid involvement, typically manifesting as ulceration with corneal exposure that responds poorly to surgical intervention given poor tissue healing …”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation